Design of a rectangular shape omega slotted microstrip patch antenna for WLAN/WiMaxwireless applications - Ahsan, M.R.; Islam, M.T.; Ullah, M.H. (Editura Academiei Romane, 2016)
In this article, an optimized rectangular shaped patch antenna loaded with inverse omega shape and horizontal slots, and feed by microstrip line is designed for WLAN/WiMAX applications. The expected resonant frequency mode and desired bandwidth are obtained through numerous simulation processes and utilizing the built-in optimizing tool in high frequency structural simulator (HFSS). The optimized design of the antenna gives impedance bandwidths (reflection coefficient S11<-10 dB) of 440 MHz (2.32 to 2.76 GHz), 570 MHz (327 to 3.84 GHz) and 1190 MHz (4.9 to 6.09 GHz) with the main resonant frequency at 2.54, 3.63 and 5.24 GHz respectively. The proposed antenna also attained appreciable gain characteristics and almost symmetrical/stable radiation patterns which can cover 2.4/5.2/5.8 GHz WLAN bands and 3.5/5.5 GHz WiMAX bands.